The Effect of Economic Growth, Unemployment, and Human Development Index on Poverty in Banda Aceh City Viewed from an Islamic Perspective - Khairul Amri; Azimah Dianah; Muhammad Putra Hartana; Zulfikri Zulfikri (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Until now, poverty is still a problem experienced all over the world. In Islam itself, there has been a balanced socio-economic environment that gives special attention to poverty alleviation, in addition to focusing on the distribution of income and wealth or reducing inequality. This research aims to determine the influence of the variables economic growth, poverty and the Islamic human development index on poverty. This type of research is quantitative using secondary data sources. This research uses documentary data collection techniques, namely the research takes data that has been printed in the form of books or magazines taken from the Aceih Central Statistics Agency for the population of the city of Banda Aceih. The results of the research show that economic growth, unemployment, economic growth, and human development index jointly influence poverty. Economic growth has an impact on poverty. unemployment has an influence on poverty and Islamic human deiveilopmeint indeix also has an influence on poverty.